Steady state analysis of single phase IPM motors by D-Q harmonic balance method - Asogwa, Jude C. (Array, 2021)
A concise steady-state analysis of a single-phase line-start permanent magnet (SPLSPM) machine is conducted from a developed d-q model using the d-q harmonic balance technique. The d-q model was developed in rotor reference frame from a phase variable model of the machine. SPLSPM whose performance indices were characterized by high torque ripples has detailed analysis docile mostly in computer simulations quite unlike the three-phase types. The main cause is not far-fetched, it was due to nonexistence of precise mathematical model in d-q rotor frame of the motor due to the unbalanced field winding, the rotor saliency and the presence of the capacitor in the auxiliary windings. Even after model has been developed, the simple traditional procedure of setting all time varying component to zero for steady-state analysis fails because the rotor position dependence on the inductance expressions could not be eliminated. The d-q harmonic-balance technique was then applied. An important feature of the harmonic balance technique was that it decoupled all equations to simple sine waveforms in a style that resembled Fourier series. Results yield torque pulsation, current and load characteristics in the steady state.